PENGARUH KOMPENSASI, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Permadi, I Made Yudi; Suana, I Wayan (E-Jurnal Manajemen, 2017)
This study aimed to determine the effect of compensation, organizational culture and work environment on employee job satisfaction either simultaneously or partially and to determine which variables are the dominant influence on job satisfaction of employees at PT Indonesia Power Bali. The respondents of this research as many as 60 employees, with stratification method (Stratified Random Sampling). The data analysis technique used to test the hypothesis is multiple linear regression analysis. Based on the analysis found that the variable compensation, organizational culture and working environment simultaneously significant effect on job satisfaction of employees at PT Indonesia Power Bali. Variable compensation, organizational culture and work environment is also positive and significant effect partially to the job satisfaction of employees at PT Indonesia Power Bali with the work environment variables as variables that influence greater job satisfaction at PT Indonesia Power Bali.
Keywords: job satisfaction; compensation; organizational culture; work environment